Biodegradation of textile Azo Dyes by Phanerochaete chrysosporium - Ferreira, Isabel C.F.R. (2011)
Azo dyes are used extensively in the textile and dyestuff industries and effluents from these industrial processes are usually resistant to biological treatment. Textile azo dyes with bioaccessible groups such as guaiacol and 2,6-dimethoxyphenol, for lignin-degrading fungus as P. chrysosporium were synthesised.